Penguatan Strategi Pemasaran Produk UMKM dan Koperasi di Kota Makassar untuk Meningkatkan Penjualan dan Pendapatan melalui Inovasi Digital - Jimar, Any; Awaliah, Andi Urfia (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
This community service activity was held in the Sulawesi University of Technology Campus Hall. The aim of this service is to strengthen the marketing strategy for MSME and Cooperative products in Makassar City. Meanwhile, the topic discussed was digital innovation which can increase sales and income of business actors. This includes a variety of digital technologies, including social media, e-commerce platforms, and data marketing that are relevant for the modern market. Participants in this activity were MSMEs, cooperative members and lecturers who attended who also had side businesses, each of whom had an interest in increasing the competitiveness of their business through marketing innovation. The results of this service show that participants have a better understanding of digitalization in marketing and higher motivation to immediately apply what they learn into practice to increase their sales and income. Thus, this activity application contributes positively to local economic growth in Makassar City.